Developing Academic Essay Writing Materials by Incorporating Experiential Learning - Cahyono, Bambang Eko Hari; Styati, Erlik Widiyani; Irawati, Lulus (Universitas Pendidikan Mandalika, 2024)
The study focuses on using a research and development strategy to develop materials for academic essay writing materials. It employs a modified version of Borg and Gall's (2003) R&D research design, with phases (1) research and information collecting, (2) developing a primary form of product, (3) validating product, (4) trying out product, (5) revising product, and (6) producing final product. The participants were the students from a private university in Indonesia. Questionnaires, interview guidelines, and an observation checklist were used to gather data. The results are found by descriptive analysis, with an 81% expert validation and an 83% trial success rate. Positive student involvement is seen, and comments emphasize how well the materials fit the goals, concepts, exercises, and group projects. Students report that the materials help the students become better writers. The materials help students write academically and push teachers to try new things in their classrooms. The success of the material points to their potential for broader application and emphasizes how crucial it is to match the materials with syllabuses, course descriptions, and learning objectives for students